A cross-national study on gender differences in suicide intent - Freeman, Aislinné (2019)
Background: Suicide accounts for over 58,000 deaths in Europe per annum, where suicide attempts are estimated to be 20 times higher. Males have been found to have a disproportionately lower rate of suicide attempts and an excessively higher rate of suicides compared to females. The gender difference in suicide intent is postulated to contribute towards this gender imbalance. The aim of this study is to explore gender differences in suicide intent in a cross-national study of suicide attempts. The secondary aims are to investigate the gender differences in suicide attempt across age and country. Methods: Data on suicide attempts (acquired from the EU-funded OSPI-Europe project) was obtained from eight regions in Germany, Hungary, Ireland and Portugal. Suicide intent data was categorized into 'Non-habitual Deliberate Self-Harm' (DSH), 'Parasuicidal Pause' (SP), 'Parasuicidal Gesture' (SG), and 'Serious Suicide Attempt' (SSA), applying the Feuerlein scale. Gender differences in intent were explored for significance by using χ2-tests, odds ratios, and regression analyses. Results: Suicide intent data from 5212 participants was included in the analysis. A significant association between suicide intent and gender was found, where 'Serious Suicide Attempts' (SSA) were rated significantly more frequently in males than females (pâ <â .001). There was a statistically significant gender difference in intent and age groups (pâ <â .001) and between countries (pâ <â .001). Furthermore, within the most utilised method, intentional drug overdose, 'Serious Suicide Attempt' (SSA) was rated significantly more often for males than females (pâ <â .005). Conclusions: Considering the differences in suicidal intent between males and females highlighted by the current study, gender targeted prevention and intervention strategies would be recommended.